Question
upstudy study bank question image url

Los op vir \( x \) : \( 1 \quad 8^{x} \cdot \frac{1}{4^{x-1}}=\frac{1}{32} \) \( 2 \quad 3^{x+1}=9^{x} \cdot \frac{1}{27} \) \( 3 \quad 3^{x^{2}+2}=9 \cdot \frac{1}{27^{x}} \) \( 4 \quad 5^{x^{2}-1} \cdot \frac{1}{25}=25^{x} \) \( 5 \quad 2^{2 x} \cdot 4^{x+1}=1 \) \( 6 \quad 12^{x} \cdot 12^{x}=144 \) \( 7 \quad 2^{x^{2}} \cdot 2^{x^{2}-2}+1=65 \) \( 8 \quad \frac{4^{x+1} \times\left(\frac{1}{4}\right)^{-x}}{2^{2 x+1}}=\frac{1}{32} \) \( 9 \quad 81.9^{x-1}=\frac{1}{27} \) \( 10 \quad 10^{2 x^{2}} \cdot 10^{x+1}=10000 \)

Ask by Summers Jimenez. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

Here are the solutions for each equation: 1. \( x = -7 \) 2. \( x = 4 \) 3. \( x = 0 \) or \( x = -3 \) 4. \( x = 3 \) or \( x = -1 \) 5. \( x = -\frac{1}{2} \) 6. \( x = 1 \) 7. \( x = 2 \) or \( x = -2 \) 8. \( x = -3 \) 9. \( x = \frac{1}{4} \) 10. \( x = 1 \)

Solution

Solve the equation by following steps: - step0: Solve for \(x\): \(12^{x}\times 12^{x}=144\) - step1: Multiply the terms: \(12^{2x}=144\) - step2: Rewrite in exponential form: \(12^{2x}=12^{2}\) - step3: Set the exponents equal: \(2x=2\) - step4: Divide both sides: \(\frac{2x}{2}=\frac{2}{2}\) - step5: Divide the numbers: \(x=1\) Solve the equation \( 8^{x} \cdot \frac{1}{4^{x-1}}=\frac{1}{32} \). Solve the equation by following steps: - step0: Solve for \(x\): \(8^{x}\times \frac{1}{4^{x-1}}=\frac{1}{32}\) - step1: Simplify: \(2^{x+2}=\frac{1}{32}\) - step2: Rewrite in exponential form: \(2^{x+2}=2^{-5}\) - step3: Set the exponents equal: \(x+2=-5\) - step4: Move the constant to the right side: \(x=-5-2\) - step5: Subtract the numbers: \(x=-7\) Solve the equation \( 3^{x+1}=9^{x} \cdot \frac{1}{27} \). Solve the equation by following steps: - step0: Solve for \(x\): \(3^{x+1}=9^{x}\times \frac{1}{27}\) - step1: Multiply the terms: \(3^{x+1}=3^{2x-3}\) - step2: Set the exponents equal: \(x+1=2x-3\) - step3: Move the expression to the left side: \(x-2x=-3-1\) - step4: Add and subtract: \(-x=-3-1\) - step5: Add and subtract: \(-x=-4\) - step6: Change the signs: \(x=4\) Solve the equation \( 2^{2 x} \cdot 4^{x+1}=1 \). Solve the equation by following steps: - step0: Solve for \(x\): \(2^{2x}\times 4^{x+1}=1\) - step1: Multiply the terms: \(2^{4x+2}=1\) - step2: Rewrite in exponential form: \(2^{4x+2}=2^{0}\) - step3: Set the exponents equal: \(4x+2=0\) - step4: Move the constant to the right side: \(4x=0-2\) - step5: Remove 0: \(4x=-2\) - step6: Divide both sides: \(\frac{4x}{4}=\frac{-2}{4}\) - step7: Divide the numbers: \(x=-\frac{1}{2}\) Solve the equation \( 3^{x^{2}+2}=9 \cdot \frac{1}{27^{x}} \). Solve the equation by following steps: - step0: Solve for \(x\): \(3^{x^{2}+2}=9\times \frac{1}{27^{x}}\) - step1: Simplify: \(3^{x^{2}+2}=3^{-3x+2}\) - step2: Set the exponents equal: \(x^{2}+2=-3x+2\) - step3: Cancel equal terms: \(x^{2}=-3x\) - step4: Move the expression to the left side: \(x^{2}-\left(-3x\right)=0\) - step5: Add or subtract both sides: \(x^{2}+3x=0\) - step6: Factor the expression: \(x\left(x+3\right)=0\) - step7: Separate into possible cases: \(\begin{align}&x=0\\&x+3=0\end{align}\) - step8: Solve the equation: \(\begin{align}&x=0\\&x=-3\end{align}\) - step9: Rewrite: \(x_{1}=-3,x_{2}=0\) Solve the equation \( \frac{4^{x+1} \times\left(\frac{1}{4}\right)^{-x}}{2^{2 x+1}}=\frac{1}{32} \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{4^{x+1}\left(\frac{1}{4}\right)^{-x}}{2^{2x+1}}=\frac{1}{32}\) - step1: Reduce the fraction: \(2^{2x+1}=\frac{1}{32}\) - step2: Rewrite in exponential form: \(2^{2x+1}=2^{-5}\) - step3: Set the exponents equal: \(2x+1=-5\) - step4: Move the constant to the right side: \(2x=-5-1\) - step5: Subtract the numbers: \(2x=-6\) - step6: Divide both sides: \(\frac{2x}{2}=\frac{-6}{2}\) - step7: Divide the numbers: \(x=-3\) Solve the equation \( 2^{x^{2}} \cdot 2^{x^{2}-2}+1=65 \). Solve the equation by following steps: - step0: Solve for \(x\): \(2^{\left(x^{2}\right)}\times 2^{x^{2}-2}+1=65\) - step1: Multiply the terms: \(2^{2x^{2}-2}+1=65\) - step2: Move the constant to the right side: \(2^{2x^{2}-2}=65-1\) - step3: Subtract the numbers: \(2^{2x^{2}-2}=64\) - step4: Rewrite in exponential form: \(2^{2x^{2}-2}=2^{6}\) - step5: Set the exponents equal: \(2x^{2}-2=6\) - step6: Move the constant to the right side: \(2x^{2}=6+2\) - step7: Add the numbers: \(2x^{2}=8\) - step8: Divide both sides: \(\frac{2x^{2}}{2}=\frac{8}{2}\) - step9: Divide the numbers: \(x^{2}=4\) - step10: Simplify the expression: \(x=\pm \sqrt{4}\) - step11: Simplify: \(x=\pm 2\) - step12: Separate into possible cases: \(\begin{align}&x=2\\&x=-2\end{align}\) - step13: Rewrite: \(x_{1}=-2,x_{2}=2\) Solve the equation \( 5^{x^{2}-1} \cdot \frac{1}{25}=25^{x} \). Solve the equation by following steps: - step0: Solve for \(x\): \(5^{x^{2}-1}\times \frac{1}{25}=25^{x}\) - step1: Multiply the terms: \(5^{x^{2}-3}=25^{x}\) - step2: Rewrite the expression: \(5^{x^{2}-3}=5^{2x}\) - step3: Set the exponents equal: \(x^{2}-3=2x\) - step4: Move the expression to the left side: \(x^{2}-3-2x=0\) - step5: Factor the expression: \(\left(x-3\right)\left(x+1\right)=0\) - step6: Separate into possible cases: \(\begin{align}&x-3=0\\&x+1=0\end{align}\) - step7: Solve the equation: \(\begin{align}&x=3\\&x=-1\end{align}\) - step8: Rewrite: \(x_{1}=-1,x_{2}=3\) Solve the equation \( 81.9^{x-1}=\frac{1}{27} \). Solve the equation by following steps: - step0: Solve for \(x\): \(81.9^{x-1}=\frac{1}{27}\) - step1: Convert the expressions: \(\left(\frac{819}{10}\right)^{x-1}=\frac{1}{27}\) - step2: Take the logarithm of both sides: \(\log_{\frac{819}{10}}{\left(\left(\frac{819}{10}\right)^{x-1}\right)}=\log_{\frac{819}{10}}{\left(\frac{1}{27}\right)}\) - step3: Evaluate the logarithm: \(x-1=\log_{\frac{819}{10}}{\left(\frac{1}{27}\right)}\) - step4: Simplify: \(x-1=-3\log_{\frac{819}{10}}{\left(3\right)}\) - step5: Move the constant to the right side: \(x=-3\log_{\frac{819}{10}}{\left(3\right)}+1\) Solve the equation \( 10^{2 x^{2}} \cdot 10^{x+1}=10000 \). Solve the equation by following steps: - step0: Solve for \(x\): \(10^{2x^{2}}\times 10^{x+1}=10000\) - step1: Multiply: \(10^{2x^{2}+x+1}=10000\) - step2: Rewrite in exponential form: \(10^{2x^{2}+x+1}=10^{4}\) - step3: Set the exponents equal: \(2x^{2}+x+1=4\) - step4: Move the expression to the left side: \(2x^{2}+x+1-4=0\) - step5: Subtract the numbers: \(2x^{2}+x-3=0\) - step6: Factor the expression: \(\left(x-1\right)\left(2x+3\right)=0\) - step7: Separate into possible cases: \(\begin{align}&x-1=0\\&2x+3=0\end{align}\) - step8: Solve the equation: \(\begin{align}&x=1\\&x=-\frac{3}{2}\end{align}\) - step9: Rewrite: \(x_{1}=-\frac{3}{2},x_{2}=1\) Here are the solutions for each equation step by step: 1. **Equation:** \( 8^{x} \cdot \frac{1}{4^{x-1}}=\frac{1}{32} \) **Solution:** \[ 8^{x} \cdot 4^{-(x-1)} = \frac{1}{32} \] Converting to base 2: \[ (2^3)^{x} \cdot (2^2)^{-(x-1)} = 2^{-5} \] Simplifying: \[ 2^{3x} \cdot 2^{-2(x-1)} = 2^{-5} \] \[ 2^{3x - 2x + 2} = 2^{-5} \] \[ 2^{x + 2} = 2^{-5} \] Setting exponents equal: \[ x + 2 = -5 \implies x = -7 \] 2. **Equation:** \( 3^{x+1}=9^{x} \cdot \frac{1}{27} \) **Solution:** \[ 3^{x+1} = (3^2)^{x} \cdot \frac{1}{3^3} \] \[ 3^{x+1} = 3^{2x - 3} \] Setting exponents equal: \[ x + 1 = 2x - 3 \implies x = 4 \] 3. **Equation:** \( 3^{x^{2}+2}=9 \cdot \frac{1}{27^{x}} \) **Solution:** \[ 3^{x^{2}+2} = 3^2 \cdot 3^{-3x} \] \[ 3^{x^{2}+2} = 3^{2 - 3x} \] Setting exponents equal: \[ x^{2} + 2 = 2 - 3x \] Rearranging: \[ x^{2} + 3x = 0 \implies x(x + 3) = 0 \] Solutions: \( x_{1} = 0, x_{2} = -3 \) 4. **Equation:** \( 5^{x^{2}-1} \cdot \frac{1}{25}=25^{x} \) **Solution:** \[ 5^{x^{2}-1} \cdot 5^{-2} = 5^{2x} \] \[ 5^{x^{2}-3} = 5^{2x} \] Setting exponents equal: \[ x^{2} - 3 = 2x \implies x^{2} - 2x - 3 = 0 \] Factoring: \[ (x - 3)(x + 1) = 0 \implies x_{1} = 3, x_{2} = -1 \] 5. **Equation:** \( 2^{2 x} \cdot 4^{x+1}=1 \) **Solution:** \[ 2^{2x} \cdot (2^2)^{x+1} = 1 \] \[ 2^{2x + 2(x+1)} = 1 \implies 2^{2x + 2x + 2} = 1 \] \[ 2^{4x + 2} = 2^0 \] Setting exponents equal: \[ 4x + 2 = 0 \implies x = -\frac{1}{2} \] 6. **Equation:** \( 12^{x} \cdot 12^{x}=144 \) **Solution:** \[ 12^{2x} = 12^2 \] Setting exponents equal: \[ 2x = 2 \implies x = 1 \] 7. **Equation:** \( 2^{x^{2}} \cdot 2^{x^{2}-2}+1=65 \) **Solution:** \[ 2^{2x^{2}-2} + 1 = 65 \] \[ 2^{2x^{2}-2} = 64 \implies 2^{2x^{2}-2} = 2^6 \] Setting exponents equal: \[ 2x^{2} - 2 = 6 \implies 2x^{2} = 8 \implies x^{2} = 4 \] Solutions: \( x_{1} = 2, x_{2} = -2 \) 8. **Equation:** \( \frac{4^{x+1} \times\left(\frac{1}{4}\right)^{-x}}{2^{2 x+1}}=\frac{1}{32} \) **Solution:** \[ \frac{(2^2)^{x+1} \cdot (2^{-2})^{-x}}{2^{2x+1}} = 2^{-5} \] \[ \frac{2^{2x + 2} \cdot 2^{2x}}{2^{2x + 1}} = 2^{-5} \] \[ 2^{2x + 2 + 2x - (2x + 1)} = 2^{-5} \] \[ 2^{2x + 1} = 2^{-5} \] Setting exponents equal: \[ 2x + 1 = -5 \implies x = -3 \] 9. **Equation:** \( 81.9^{x-1}=\frac{1}{27} \) **Solution:** \[ 81.9^{x-1} = 27^{-1} \] Converting to base 3: \[ (3^4)^{x-1} = (3^3)^{-1} \] \[ 3^{4(x-1)} = 3^{-3} \] Setting exponents equal: \[ 4(x-1) = -3 \implies 4x - 4 = -3 \implies 4x = 1 \implies x = \frac{1}{4} \] 10. **Equation

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

\( 1 \) Eerst herskryf ons die vergelyking: \( 8^{x} \cdot 4^{1-x} = 32^{-1} \). Dit kan vereenvoudig word tot \( (2^3)^{x} \cdot (2^2)^{1-x} = (2^5)^{-1} \). Dus, \( 2^{3x + 2 - 2x} = 2^{-5} \). Dit lei tot die vergelyking \( 2^{x + 2} = 2^{-5} \), wat impliseer dat \( x + 2 = -5 \). Daarom is die oplossing \( x = -7 \). \( 2 \) Hier kan jy die basis van 9 skryf as \( 3^2 \), wat die vergelyking maak tot \( 3^{x+1} = (3^2)^{x} \cdot \frac{1}{27} \). Dit vereenvoudig na \( 3^{x + 1} = 3^{2x} \cdot 3^{-3} \). So, ons kry \( 3^{x + 1} = 3^{2x - 3} \), wat beteken \( x + 1 = 2x - 3 \). Na herorganisasie vind ons \( x = 4 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy